GIS-Based Landslide Susceptibility Mapping Using Weighted Overlay in Ogan Komering Ulu - Juliansyah, Ilham Rahmat; Harnani, Harnani; Nurohim, Dede (Jambura Geoscience Review, 2026)
Landslides pose a major hazard in Ogan Komering Ulu Regency, South Sumatra, where rugged relief, high rainfall, and land-use change can reduce slope stability. This study develops a GIS-based landslide susceptibility map using the weighted overlay method to support disaster mitigation and spatial planning. Five conditioning factors—slope, rainfall, geology, soil type, and land use—were prepared as thematic layers from DEMNAS topography, CHIRPS rainfall estimates interpolated using Inverse Distance Weighting, geological shapefiles from Ina-Geoportal, soil information from the FAO–UNESCO Digital Soil Map of the World, and land-cover data from the Indonesian Base Map (RBI). Each factor was reclassified into susceptibility classes, assigned scores, and weighted according to its relative influence on landslide occurrence, then integrated through overlay analysis to produce a composite susceptibility index. The index was classified into low, moderate, and high susceptibility zones. The results indicate that moderate susceptibility dominates most of the study area, while high-susceptibility zones are concentrated in hilly to mountainous terrains with steep slopes and unfavorable geological and soil conditions. Model performance, evaluated using a landslide inventory and the Receiver Operating Characteristic curve, produced an Area Under the Curve value of 0.715, indicating moderate predictive accuracy. The susceptibility map provides actionable spatial information to prioritize monitoring and guide land-use management in Ogan Komering Ulu.